'A creeping phenomenon': the association between rainfall and household food insecurity in the district of iLembe, KwaZulu-Natal. (7th February 2021) - Drysdale, Roisin E.; Moshabela, Mosa; Bob, Urmilla
ABSTRACT: The effects of rainfall variability and droughts on food production are well established. However, in South Africa, the association between rainfall, droughts and household food insecurity is not well known. The aim of this paper was to measure and compare household food insecurity during and after a drought, and to assess the association between rainfall and food insecurity. Using a comparative study design, two cross-sectional household surveys took place in November 2016 and November 2017. Food insecurity was measured using the Coping Strategies Index. Data was analysed using descriptive statistics and multiple linear regression. The study found a positive association between increasing rainfall and food insecurity, the strength of which decreased during Round 2 of data collection. The proportion of households facing no food insecurity increased, as did those facing high or severe food insecurity. Households in Round 2 appeared to have better diet diversity, although there was an increase in the frequency of some coping strategies, including those relying on less expensive foods on a daily basis. The study highlights the delayed and prolonged effects of a drought and recommends research be carried out to investigate the socio-economic factors associated with increasing food insecurity in the iLembe district of KwaZulu-Natal.